A Teager–Kaiser Energy Operator and Wavelet Packet Transform for Bearing Fault Detection. Issue 3 (3rd July 2018) - Azergui, Mohamed; Abenaou, Abdenbi; Bouzahir, Hassane
Abstract: The excellent features of bearing vibration signal are gainful to make accurate diagnosis results on the type of bearing damage. In this paper, a signal analysis technique based on wavelet packet transform (WPT) and Teager– Kaiser energy operator (TKEO) are presented. The objective of the proposed method is to demonstrate the effectiveness of the statistical parameters as the principal criterion for selecting the optimal frequency band in order to extract fault characteristics from vibration signal. Then, the TKEO is employed to track the modulation energy. The simulation and experimental results indicate that the proposed method enhances performances for detecting the bearing faults. Abstract :